FAKTOR â FAKTOR YANG MEMPENGARUHI KETERANDALAN PELAPORAN KEUANGAN DAERAH - Septiawan, Oky; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to examine empirically the influence of human resources quality, the use of information technology, and internal control to the reliability of local government financial reporting. The respondents in this research is all structural officials who are involved in the local government financial reporting. The structural officials who are involved in this research are Local Official Financial Management (PPKD) and Local Financial Management Working Unit (SKPKD). This research has selected theLocal Apparaturs Organization of Surabaya city as the population which consists of Local Secretariats, Local Inspectorate, Local Agencies. The sample collection technique has been done by using purposive sampling which means that the sample collection is based on particular consideration and criteria. The data analysis technique has been carried out by using multiple linear regressions analysis. It has been found from the result of the research that human resources quality, the use of information technology, and internal control are suitable as the explanatory variable and it gives positive influence to the financial reporting reliability.Keywords: Human resources quality, the use of information technology, internal control